Is the rest of the EU missing out on REITs? - Andrius Grybauskas; Vaida Pilinkiene (European Journal of Management and Business Economics (EJM&BE), 2020)
Purpose The purpose of this paper is to investigate whether real estate investment trusts (REITs) have any significant cost-efficiency advantages over real estate operating companies (REOCs). Design/methodology/approach The data for listed companies were extracted from the Bloomberg terminal. The authors analyzed financial ratios and conducted a non-parametric data envelope analysis (DEA) for 534 firms in the USA, Canada and some EU member states. Findings The results suggest that REITs were much more cost-efficient than REOCs by all the parameters in the DEA model during the entire three-year period under consideration. Although the debt-to-equity levels were similar, REOCs were more relying on short-term than long-term maturities, which made them more vulnerable against market corrections or shocks. Being larger in asset size did not necessarily guarantee greater economies of scale. Both - the cases of increasing economies of scale and diseconomies - were detected. The time period 2015-2017 showed the general trend of decreasing efficiency. Originality/value Very few papers on the topic of REITs have attempted to find out whether a different firm structure displays any differences in efficiency. Because the question of REITs and sustainable growth of the real estate market has become a prominent issue, this research can help EU countries to consider the option of adopting a REIT system. If this system were successfully implemented, the EU member states could benefit from a more sustainable and more rapid growth of their real estate markets.
Keywords: 650; Efficiency; DEA; REITs; Real estate; REOCs